Preparing a Speech for Participating in Round Table Discussions in C1 Level (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses the process of preparing a speech for participating in round table discussions at the C1 level of language proficiency. It highlights the importance of understanding the topic, organizing thoughts, and using appropriate language to convey ideas effectively. The abstract also emphasizes the need to address counterarguments, use transition words, and practice delivery for fluency and confidence. It concludes by emphasizing active participation and engagement in discussions to make the most of the C1 level proficiency.